In the Dyson series, it is known that: \begin{align} {\cal T}\exp\left[-\frac{i}{\hbar}\int_0^tH(t')dt'\right] &= I - \frac{i}{\hbar} \int_{0}^{t} dt' H(t') + \left(-\frac{i}{\hbar}\right)^2 \frac{1}{2} \mathcal{T}\left(\int_{0}^{t} dt' H(t')\right)^2 \\& \quad + \left(-\frac{i}{\hbar}\right)^3 \mathcal{T}\left(\frac{1}{3!}\left(\int_{0}^{t} dt' H(t')\right)^3\right) \cdots \\ & = I - \frac{i}{\hbar}\int_{0}^{t}dt' H(t') + \left(-\frac{i}{\hbar}\right)^2 \int_{0}^{t}dt' \int_{0}^{t'}dt'' H(t') H(t'') \\ & \quad + \left(-\frac{i}{\hbar}\right)^3 \int_{0}^{t}dt' \int_{0}^{t'}dt'' \int_{0}^{t''}dt''' H(t') H(t'') H(t''') +\cdots \end{align}

I know that by showing the "square" integration is equal to two "triangle" integrals, we have $$\int_{0}^{t}dt'\int_{0}^{t'}dt'' H(t')H(t'') = \frac{1}{2}\mathcal{T}\left\{\left(\int_{0}^{t}dt'H(t')\right)^2\right\}.$$

I know the R.H.S is the integral of square. But why is $\mathcal{T}$ needed in$$ \mathcal{T}\left\{\left(\int_{0}^{t}dt'H(t')\right)^2\right\}~?$$

Since $$\left(\int_{0}^{t}dt'H(t')\right)^2 = \left(\int_{0}^{t}dt'H(t')\right)\left(\int_{0}^{t}dt'H(t')\right),$$

even by changing the dummy variable $$\left(\int_{0}^{t}dt'H(t')\right)^2 = \left(\int_{0}^{t}dt'H(t')\right)\left(\int_{0}^{t}dt''H(t'')\right),$$ the two single integral terms in the product mean the same thing. Without messing around this product form into a double integral form, why $\mathcal{T}$ is needed in this particular term even before changing of dummy variable?



$$\int_0^t dt'\int_0^{t}dt'' \mathcal{T}\left(H(t')H(t'')\right)$$ \begin{align} &= \int_0^t dt'\int_0^{t'}dt'' \mathcal{T}\left(H(t')H(t'')\right) \\ & \qquad +\int_0^t dt'\int_{t'}^{t}dt'' \mathcal{T}\left(H(t')H(t'')\right) \\&= \int_0^t dt'\int_0^{t'}dt'' H(t')H(t'') \\ & \qquad +\int_0^t dt'\int_{t'}^{t}dt''H(t'')H(t') \end{align}

The last line follows from the definition of time ordering: in the first integral $t''<t'$ checking the limits of integration, so $\mathcal{T}\left(H(t')H(t'')\right)=H(t')H(t'')$, similarly for the second integral.

As you mentioned using the trick with triangles and squares, we can change the second integral to $$\int_0^t dt''\int_{0}^{t''}dt'H(t'')H(t')$$

This is the upper triangle in a $(t',t'')$ diagram. Now relabel dummy variables $$\int_0^t dt'\int_{0}^{t'}dt''H(t')H(t'')$$

And so recombining we get $$\int_0^t dt'\int_0^{t}dt'' \mathcal{T}\left(H(t')H(t'')\right)=2\int_0^t dt'\int_{0}^{t'}dt''H(t')H(t'').$$

Let's take a reasonably straightforward example:

$$H(t)=t\sigma_y +(1-t)\sigma_x$$

$H(0)$ doesn't commute with $H(1)$.

Let $$I(t)=\int_0^t dt' H(t')=\frac{t^2}{2}\sigma_y +t(1-\frac{t}{2})\sigma_x$$

Then \begin{align}I(t)^2 &=\int_0^t dt_1 \int_0^t dt_2 H(t_1) H(t_2)\\ &=(\frac{t^4}{4}+t^2(1-t/2)^2)I+\frac{t^3}{2}(1-t/2)\{\sigma_y,\sigma_x\}=t^2(\frac{t^2}{2}-t+1)I \end{align}

Now with time ordering \begin{align} J(t)=\int_0^t dt_1 \int_0^t dt_2 \mathcal{T}\left(H(t_1) H(t_2)\right)&=\int_0^t dt_1\int_0^{t_1}dt_2 H(t_1)H(t_2)+\int_0^t dt_1\int_{t_1}^{t}dt_2 H(t_2)H(t_1)\\ &=\int_0^t dt_1 H(t_1)\int_0^{t_1}dt_2 H(t_2)+\int_0^t dt_1\int_{t_1}^{t}dt_2 H(t_2)H(t_1)\\ &= \int_0^t dt_1 H(t_1)I(t_1)+\int_0^t dt_1 \left(I(t)-I(t_1)\right)H(t_1)\end{align}

It's useful to commute some commutators:

\begin{align}\left[H(t_1),H(t_2)\right]&=\left[ t_1\sigma_y +(1-t_1)\sigma_x , t_2\sigma_y +(1-t_2)\sigma_x \right]\\ &=t_1(1-t_2)[\sigma_y,\sigma_x]+t_2(1-t_1)[\sigma_x,\sigma_y]\\&=2i(t_2-t_1)\sigma_z\end{align} And

\begin{align} \left[H(t_1),I(t_1)\right] &=\left[ H(t_1) \,, \int_0^{t_1} dt_2 H(t_2)\right]\\&= \int_0^{t_1} dt_2 \left[ H(t_1) \,,H(t_2)\right]\\&=-it_1^2\sigma_z \end{align}

So \begin{align} J(t)&=\int_0^t dt_1 \left[H(t_1),I(t_1)\right] +I(t)^2\\&=-i\frac{t^3}{3}\sigma_z+I(t)^2 \end{align}

Finally lets consider

$$K(t)=2\int_0^t dt_1 \int_0^{t_1} dt_2 H(t_1)H(t_2) \overset{?}{=} J(t)$$


\begin{align} K(t)=2\int_0^t dt_1 H(t_1)I(t_1)&=\int_0^t dt_1 \left[H(t_1),I(t_1)\right]+\{H(t_1),I(t_1)\}\\&=-i\frac{t^3}{3}\sigma_z + \int_0^t dt_1 \{H(t_1),I(t_1)\} \end{align}


\begin{align} \{H(t_1),I(t_1)\}=\int_0^{t_1} dt_2 \{H(t_1),H(t_2)\}&=\int_0^{t_1} dt_2 \left(2t_1 t_2 +2(1-t_1)(1-t_2)\right)I\\&=I\left(t_1^3 +2(1-t_1)(1-\frac{t_1}{2})t_1\right) \end{align}

Finally if you multiply out and integrate you will find that

$$K(t)=-i\frac{t^3}{6}\sigma_z +t^2(\frac{t^2}{2}-t+1)I=-i\frac{t^3}{6}\sigma_z+I(t)^2=J(t)$$

As an extra note, the definition I've seen for the time ordered exponential is (with the convention that the first term is the identity operator):

$$\mathcal{T}\exp\left(-i/\hbar \int_0^t h(t')dt'\right):=\sum_{n=0}^\infty \frac{1}{n!}\left(\frac{-i}{\hbar}\right)^n \int_0^t dt_1 \ldots\int_0^t dt_n \mathcal{T}\left(H(t_1)\ldots H(t_n)\right) $$

And for the Dyson series:

$$U^\dagger(t,0)=I+\frac{-i}{\hbar}\int_0^t dt' H(t')+\left(\frac{-i}{\hbar}\right)^2\int_0^t dt'\int_0^{t'}dt'' H(t')H(t'')+\ldots$$

The above reasoning at least formally suggests them to be equivalent.

  • $\begingroup$ But I starts from $\int_0^t dt'\int_0^{t}dt'\mathcal{T}\left(H(t')H(t')\right)$ where the time index is the same. Why is time ordering still needed there? $\endgroup$ – diff Jul 21 '16 at 11:36
  • $\begingroup$ @diff You won't get the same answer is the main reason. Here's an example to show why you need separate dummy variables: Let $I=\int_0^t dx \,x=t^2/2$, then $I^2=t^4/4$, however $\int_0^t dx \int_0^t dx [\,x\cdot x]= \int_0^t dx \,t^3/3=xt^3/3\big|_0^t=t^4/3$. You'll get the correct answer if you evaluate $\int_0^t dx \int_0^t dx' \,x\,x'$ $\endgroup$ – snulty Jul 21 '16 at 11:45

Time-ordering is needed if the Hamiltonians $H(t^{\prime})$ and $H(t^{\prime\prime})$ at different times do not commute.

Example: If the Hamiltonian is $$H(t) ~=~ \left\{\begin{array}{ccl} \color{Red}{\diamondsuit}&\text{if}& t<0, \cr \clubsuit &\text{if}& t>0, \end{array} \right.$$ then the non-time-ordered product $(\int\! dt ~H(t))^2$ has all $2\times2=4$ possible terms: $$\clubsuit\clubsuit , \quad \color{Red}{\diamondsuit}\color{Red}{\diamondsuit}, \quad \clubsuit\color{Red}{\diamondsuit}, \quad \text{and} \quad \color{Red}{\diamondsuit}\clubsuit.$$ In contrast, the time-ordered product $T\left[(\int\! dt~ H(t))^2\right]$ does not contain terms with anti-chronological ordering $\color{Red}{\diamondsuit}\clubsuit$.

See also this related Phys.SE post for the necessity to introduce time-ordering.

  • $\begingroup$ Specifically in that order $\color{Red}{\diamondsuit}\clubsuit$ right? $\endgroup$ – snulty Jul 21 '16 at 14:01
  • $\begingroup$ $\uparrow$ Yes. $\endgroup$ – Qmechanic Jul 21 '16 at 18:09

You have to keep in mind that an integral is (more or less) a sum, and therefore in a double or multiple integral, you have cross terms that have to be correctly time-ordered. The usual Riemann integral does not take in account the non-commuting nature of its integrand, so you have to make it manifest with the time-ordering symbol $\mathcal{T}$.

Imagine for a moment that you discretize your integral. Without the time-ordering symbol $\mathcal{T}$, you would get $$ \left(\int_0^t dt' H(t') \right)^2 = \int_0^t dt' \int_0^t dt'' H(t') H(t'') \to \sum_{j=0}^{t/\Delta t} \sum_{k=0}^{t/\Delta t} (\Delta t)^2 H(j\Delta t) H(k\Delta t)$$ Here, all the $j$ ($t'$ in the continuous version) terms come before the $k$ ($t''$), regardless if $t' > t''$.

On the other hand, the same integral with the time-ordering symbol would be \begin{align} \mathcal{T}\left(\int_0^t dt' H(t') \right)^2 & = \mathcal{T}\left[\int_0^t dt' \int_0^t dt'' H(t') H(t'')\right] \\ & \to \sum_{j=0}^{t/\Delta t} \sum_{k=0}^{t/\Delta t} (\Delta t)^2 \mathcal{T} [H(j\Delta t) H(k\Delta t)] \\ & = \sum_{j=0}^{t/\Delta t} \sum_{k=0}^{j} (\Delta t)^2 H(j\Delta t) H(k\Delta t) \\ & \qquad + \sum_{j=0}^{t/\Delta t} \sum_{k=j}^{t/\Delta t} (\Delta t)^2 H(k\Delta t) H(j\Delta t) \end{align} Now, the two Hamiltonians are correctly time-ordered.

The $\mathcal{T}$ in your case comes from the series expansion of the time-ordered exponential $$\mathcal{T}\exp\left(-\frac{i}{\hbar}\int_0^t dt' H(t)\right).$$

tl;dr: The $\mathcal{T}$ determines the prescription for the Riemann sums when you're integrating non-commuting objects.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.